The Role of Popular Culture and the Intensity of Online Interaction on Language Variation of Urban Indonesian Adolescents - Ida Bagus Rai Putra; I Wayan Deddy Sumantra; I Wayan Gede Lamopia; Gek Diah Desi Sentana; I Gede Bagus Wisnu Bayu Temaja (Eastasouth Institute, 2026)
The expansion of digital technology and the widespread influence of global popular culture have significantly shaped the communication patterns of urban Indonesian adolescents, leading to the emergence of new linguistic variations in everyday interaction. This study aims to analyze the role of popular culture and the intensity of online interaction in shaping language variation among urban youth in digital spaces. A mixed-method approach was employed, combining social media usage surveys, digital content observation, and limited interviews with adolescents in urban environments. The findings indicate that popular culture particularly music, fashion trends, and global online content encourages the adoption of foreign vocabulary, code-switching, and symbolic digital expressions. Meanwhile, high levels of online interaction accelerate the diffusion of linguistic innovations, strengthen group identity, and establish new communication norms among adolescents. These results demonstrate that urban youth language variation is not merely a linguistic phenomenon but also a social practice closely related to identity construction, lifestyle, and participation in digital culture.